An experimental study on mechanical behavior and failure mechanism of sleeved fasteners and conventional bolt for composite interference-fit joints. (January 2022) - Xu, Guanhua; Zhang, Kaifu; Cheng, Hui; Luo, Bin; Liang, Biao; Cheng, Yi; Li, Hailin
Abstract: This paper aims to reveal the effect of different fasteners on the mechanical behavior and failure mechanism of composite interference-fit joints under assembly and quasi-static loading conditions. Composite single-lap and double-lap joints joined by conventional bolt and sleeved fasteners were focused on and their joint deformation and failure were characterized by the means of digital image correlation (DIC) and scanning electron microscope (SEM). Differences in failure load, bearing strength, joint stiffness, joint deformation and failure mode under different fastener fit types including neat-fit, interference-fit and interference-fit with sleeved fasteners were evaluated. Results show that the interference-fit with sleeved fasteners significantly improves the bearing performance of the joints. Under the same interference-fit, the initial failure load and ultimate bearing strength of sleeved fasteners for the composite double-lap joints are 33% and 12% greater than conventional bolt respectively. Moreover, the interference-fit with sleeved fasteners strengthens the joint bending stiffness and further alleviates the surface strain concentration compared with the interference-fit with conventional bolt. The conclusions in this article have a guiding significance for the design of composite interference-fit joints. Highlights: Mechanical behavior and failure mechanism for composite joints were investigated. Composite joints joined by conventional bolt and sleeved fasteners were focused on. Joint deformation and its failure were characterized by the means of DIC and SEM. The interface damage behavior of fastener installation process was analyzed. The bearing behavior and failure mode after final failure were evaluated.